2020
DOI: 10.3390/d12080305
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Distribution of Five Timber Forest Species in Amazonas, Northeast Peru: Contributions towards a Restoration Strategy

Abstract: Forest and land degradation is a serious problem worldwide and the Peruvian National Map of Degraded Areas indicates that 13.78% (177,592.82 km2) of the country’s territory is degraded. Forest plantations can be a restoration strategy, while conserving economically important species affected by climate change and providing forestry material for markets. This study modelled the species distribution under current conditions and climate change scenarios of five Timber Forest Species (TFS) in the Amazonas Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 64 publications
1
19
0
1
Order By: Relevance
“…We adapted the methodologies proposed by OSINFOR [43] and Hengl et al [44] and applied by Rojas et al [45] to assess the biogeographical distribution of the ten forest timber species. The detailed methodological framework adopted by this study is shown in Figure 2.…”
Section: Methodological Designmentioning
confidence: 99%
See 1 more Smart Citation
“…We adapted the methodologies proposed by OSINFOR [43] and Hengl et al [44] and applied by Rojas et al [45] to assess the biogeographical distribution of the ten forest timber species. The detailed methodological framework adopted by this study is shown in Figure 2.…”
Section: Methodological Designmentioning
confidence: 99%
“…m 3 (r)) ( Table 1; Supplementary Table S1). Of these 10 species, five were evaluated by Rojas et al [45] as being the most exploited in 2018. However, in this study, in addition to the restoration approach, they were analyzed under a system of conservation and coexistence among a greater number of species.…”
Section: Selection and Collection Of Occurrences Of The Most Importanmentioning
confidence: 99%
“…This study showed that MaxEnt based SDM tools that will allow the identification and prediction of geographic spaces with edaphoclimatic, topographic, equal or similar characteristics of the presence data [46]. Previous studies have used MaxEnt, this being the most accepted [47] and was related to the distribution of timber species at the regional [21,22], national [48][49][50] level and the identification of niches ecological for C. odorata in Peru [51].…”
Section: Discussionmentioning
confidence: 99%
“…We have used the logistic output format to obtain the model of the 10 species evaluated, by generating a raster of continuous values in a range from 0 to 1. The raster obtained was reclassified into four ranges: (1) "High potential" habitat (> 0.6), (2) "moderate" habitat (0.4-0.6), (3) "low" habitat (0.2-0.4) and ( 4) "no potential" habitat (<0.2) [21,22,25,44].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation